The Socialization of School Level Waste Management to SMP IT Baitul Jannah Teachers as an Effort Towards Environmentally Friendly Schools - Yanti, Demi Dama (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M), Institut Teknologi Sumatera, Lampung, Indonesia., 2022)
Abstract SMP IT Baitul Jannah is one of schools existing at Pramuka road No. 43, Kemiling, Bandar Lampung. Waste management at there is just only collecting and carrying garbage. Activities such sorting, reducing and reusing are not applied in school environment. It is caused lack of socialization about waste management at there. In applying Adiwiyata program, awareness and knowledge are needed to keep environment by people in SMP IT Baitul Jannah. The solution to handle problem about garbage in there is by giving socialization about trash handling and utilization to the teachers due to they are role model for their students. Because of waste management socialization, there is 70% competency enhancement among 30 audience taking the test. Keywords: garbage, socialization, waste management